PENGARUH MODIFIKASI LUBANG BUANG TERHADAP DAYA DAN TORSI PADA SEPEDA MOTOR 2 TAK - Hadi Al-Rasyid, Muhammad; Anam, Khoirul; Towijaya, Towijaya (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
Gasoline engine is one type of internal combustion engine that is widely used as a source of power for vehicles. Gasoline engines produce power from the combustion of fuel in the cylinders. In line with the development of science and technology, there are many improvements and developments of components to add power and torque. The purpose of this study was to determine the effect of modified exhaust cylinder block on power and torque on a 2 stroke Yamaha f1zr motorcycle with a modified exhaust hole height of 26 mm and a standard exhaust hole of 34 mm with a dynotest test to determine power and torque from 2500 RPM to RPM. 8000. The test results show that the maximum power at the modified exhaust hole is 12.5 HP at 7750 RPM while the standard exhaust port gets a maximum power of 11.5 HP at 7750 RPM. For the modified exhaust hole maximum torque is 11.36 Nm at 7750 RPM rotation while the standard exhaust hole obtains a maximum torque of 10.06 Nm at 7750 RPM rotation.Keywords: Power, torque, exhaust hole